Complete rat spinal cord transection as a faithful model of spinal cord injury for translational cell transplantation - Lukovic, Dunja; Moreno-Manzano, Victoria; Lopez-Mocholi, Eric; Rodriguez-Jiménez, Francisco Javier; Jendelova, Pavla; Sykova, Eva; Oria, Marc; Stojkovic, Miodrag; Erceg, Slaven (Scientific reports, 2015)
Spinal cord injury (SCI) results in neural loss and consequently motor and sensory impairment below the injury. There are currently no effective therapies for the treatment of traumatic SCI in humans. Various animal models have been developed to mimic human SCI. Widely used animal models of SCI are complete or partial transection or experimental contusion and compression, with both bearing controversy as to which one more appropriately reproduces the human SCI functional consequences. Here we present in details the widely used procedure of complete spinal cord transection as a faithful animal model to investigate neural and functional repair of the damaged tissue by exogenous human transplanted cells. This injury model offers the advantage of complete damage to a spinal cord at a defined place and time, is relatively simple to standardize and is highly reproducible.
Keywords: Disease Models, Animal; Cell Transplantation; Embryonic Stem Cells; embryonální kmenové buňky; modely nemocí na zvířatech; krysa rodu Rattus; translační biomedicínský výzkum; Translational Research, Biomedical; Animals; lidé; Female; ženské pohlaví; Spinal Cord Injuries; transplantace buněk; poranění míchy; zvířata; Humans; Rats